GDR Atomic Bean Industry Development Strategy In Nagari Panyalaian, X Koto District Tanah Datar Regency - Fitri Dahlia; Afriva Khaidir (Ridwan Institute, 2023)
The purpose of this study is to find out how the GDR atomic bean industry and its development strategy. This research method begins with a qualitative picture and then is supported by SWOT analysis techniques. Sampling using purposive sampling technique. The results of this study found that. The strength in the development of the GDR atomic bean industry is strong branding, consistency of taste, consistency of prices, clear work system, family work culture and permission from the health office. Weaknesses in processing goods still using human resources so that they still depend on humans and have not focused on developing marketing aspects. The opportunity in the development of the GDR atomic bean industry is that there is no rival to the atomic bean industry in West Sumatra, thus accelerating business development to other regions and with high-quality product quality and at affordable prices can compete with other competitors. The threat in the GDR atomic bean industry is the existence of competitors of other brands of atomic beans and the decline in public buying interest at certain times